2001
DOI: 10.1074/jbc.m006677200
|View full text |Cite
|
Sign up to set email alerts
|

Sub-second Kinetics of the Nitric Oxide Receptor, Soluble Guanylyl Cyclase, in Intact Cerebellar Cells

Abstract: Soluble guanylyl cyclase (sGC) catalyzes cGMP synthesis and serves as a physiological receptor for nitric oxide (NO). Recent evidence indicates that key properties of sGC within cells differ from those of purified sGC. We have devised a technique for resolving NO-stimulated sGC activity in cells on a sub-second time scale, enabling the first quantitative description of the kinetics of the enzyme within its natural environment. Upon release of NO from a caged derivative, sGC became activated without any lag obs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
82
1

Year Published

2001
2001
2013
2013

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 105 publications
(94 citation statements)
references
References 31 publications
11
82
1
Order By: Relevance
“…Recent evidence has revealed that the NO receptor behaves substantially differently within intact cells from its behavior in the test tube. In particular, the rate of deactivation is Ϸ25-fold faster than even the highest estimate for purified sGC (27), and the receptor exhibits a desensitizing profile of catalytic activity (28). The mechanistic details of this discrepancy in behavior are unknown at present.…”
Section: Discussionmentioning
confidence: 98%
“…Recent evidence has revealed that the NO receptor behaves substantially differently within intact cells from its behavior in the test tube. In particular, the rate of deactivation is Ϸ25-fold faster than even the highest estimate for purified sGC (27), and the receptor exhibits a desensitizing profile of catalytic activity (28). The mechanistic details of this discrepancy in behavior are unknown at present.…”
Section: Discussionmentioning
confidence: 98%
“…The receptors are ␣␤-heterodimers, of which two main isoforms, ␣ 1 ␤ 1 and ␣ 2 ␤ 1 , exist at differing levels in different tissues (5). Studies on purified receptors (6) and intact cells (7) suggest that activation of GC occurs very rapidly, within a few ms or less of adding NO, and complete deactivation in cells (upon removal of NO) requires only about 500 ms (7). Furthermore, when studied in isolation, the receptors are highly sensitive NO detectors, with only about 1 nM being needed to evoke half-maximal GC activity (8).…”
mentioning
confidence: 99%
“…Briefly, purified sGC in vitro has an EC 50 of 85-250 nM of NO [217,218], is fully activated by NO within a few milliseconds [219], remains constantly active upon available substrate and ligand, and deactivates in a seconds-to-minutes range after NO disappears from the reaction scene [220,221]. sGC in vivo exhibits EC 50 of 45 nM of NO and an approximately 25-fold faster deactivation [222]. Downstream cGMP signaling cascades include stimulation of G-family protein kinases, altering cGMP-gated ion channels, and modulation of cGMP-binding phosphodiesterases [206].…”
Section: No Targetsmentioning
confidence: 99%